Experiences of HIV-related stigma among HIV-positive older persons in Uganda – a mixed methods analysis - Kuteesaa, Monica O.; Wright, Stuart; Seeley, Janet; Mugisha, Joseph; Kinyanda, Eugene; Kakembo, Frederick; Mwesigwa, Richard; Scholten, Francis (Journal of Social Aspects of HIV/AIDS, 2014)
There is limited data on stigma among older HIV-infected adults in sub-Saharan Africa. We describe the experiences of stigma and disclosure in a cohort of HIV-positive older people in Uganda. Using data from the Wellbeing of Older Peoples’ Study of Kalungu (rural site) and Wakiso district (peri-urban site) residents, we measured self-reported stigma levels for 183 respondents (94 on antiretroviral therapy (ART); 88, not on ART) using a stigma score generated using three questions on stigma perceptions where 0 meant no stigma at all and 100 was maximum stigma. Based on two questions on disclosure, an overall score was computed. High disclosure was assigned to those who often or very often disclosed to the family and were never or seldom afraid to disclose elsewhere. We examined the experiences of HIV stigma of 25 adults (52% females) using semi-structured, open-ended interviews and monthly oral diaries over one year. Mean age of the respondents was 70 years (range 60–80 years) and 80% of all respondents were enrolled in ART. Interview transcripts were analysed using thematic content analysis. Overall, 55% of respondents had a high disclosure score, meaning they disclosed easily, and 47% had a high stigma score. The stigma scores were similar among those with high and low disclosure scores. In multivariate analyses with disclosure and stigma scores as dependent variables none of the respondents’ characteristics had a significant effect at the 5% level. Qualitative data revealed that stigma ranges from: (1) perceptions (relatively passive, but leading to behaviour such as gossip, especially if not intended maliciously); to (2) discriminatory behaviour (active or enacted stigma; from malicious gossip to outright discrimination). Despite the relatively high levels of disclosure, older people suffer from high levels of stigma of various forms apart from HIVrelated stigma. Efforts to assess for different forms of stigma at an individual level deserve greater attention from service providers and researchers, and must be context specific.
Keywords: disclosure; discrimination; HIV; older people